Relationship between oil price changes and the South African stock market returns: a nonlinear ARDL analysis - Habana, Athenkosi (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Understanding the factors that influence oil price volatility and how they affect the stock market is crucial for decision-making, planning, and forecasting by governments, companies, and individuals. The aim of this study is to analyze the relationship between oil prices and stock market returns of selected JSE stock indices. A nonlinear ARDL model is used to study the interaction between changes in oil prices and the South African stock market. Monthly data covering the period from January 2010 to December 2022 is utilized in the study. The main findings of the study show that in the short run negative changes in oil prices have a statistically significant positive impact that on stock returns of the All-Share, Financials and Resources indices, while it is insignificant for the Industrials index stock returns. On the other hand, positive changes in oil prices have a negative and insignificant impact on all the stock returns of the indices. Therefore, in the short-run there is no nonlinear relationship between oil prices and the stock returns of the indices. In the long-run, the impact of oil prices on stock returns of the All Share, Financials and Resources indices is nonlinear or asymmetric. The impact of oil price changes on the stock indices varies across the indices. An increase in oil prices has a negative and statistically significant impact on stock returns of the All Share, Financials and Resources index. Conversely, a decrease in oil prices has a positive and significant impact on All Share, Financials and Resources index stock returns in the long-run. The impact of positive and negative changes in oil prices is insignificant for the Industrials index stock returns. Therefore, these finding makes it possible for investors or portfolio managers to better mitigate the negative consequences of unforeseen events and adapt their investment plans to hedge against variations in the price of oil.
Keywords: Stock market index -- South Africa; Stock exchanges -- South Africa; Petroleum products Prices -- South Africa; Autoregression (Statistics); JSE Securities Exchange -- South Africa